Polymicrobial infection confined to Ahmed glaucoma shunt - Jessica C. Lee; Bret M. Evers; Dominick Cavuoti; R. Nick Hogan; Karanjit S. Kooner (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To present a case of a unique complication of an Ahmed glaucoma shunt. The pathological and immunohistochemical findings will also be discussed. Observations: A 58-year-old woman with glaucoma secondary to Marfan syndrome and cataract surgery developed exposure of an Ahmed glaucoma tube, intraluminal white inflammatory material, and low-grade endophthalmitis five years after insertion. The patient was treated with topical and oral antibiotics and successfully underwent removal and replacement of the shunt. Pathologic analysis of the intraluminal contents revealed a bacterial infiltrate of mixed morphology. Conclusions and Importance: Concurrent tube exposure, intraluminal exudates, and endophthalmitis is a rare but potentially serious complication of glaucoma drainage device surgery. When this complication is encountered, prompt medical and surgical intervention is necessary to prevent significant vision loss. Ultimately, the glaucoma shunt may be revised, replaced, or removed altogether from the eye.